PERANCANGAN IKLAN LAYANANMASYARAKAT TENTANG CAR FREE DAY DI KOTA PADANG DALAM MEDIA BALIHO - RAJAKU MELIALA, Dr. Budiwirman, M.Pd, Drs. Ismanadi Uska (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Car Free Day is a car-free day which aims to reduce air pollution polluted by motor vehicles and also has a special purpose, namely that people care about the environment that is clean and comfortable "Environmentally Friendly". The government set Sulaiman Khatib Padang region into a car-free area which was held on Sunday, exactly on October 30, 2011 for 3 (three) hours starting at 06:00 to 9:00 pm in the Sulaiman Khatib named Car &Motorcycle Free Day.Design method used is the SWOT analysis. Advantages of Car Free Day activities, namely: (1) to reduce the capacity of the air pollution pollution caused by motor vehicles, (2) the presence of Car Free Day is, making a new culture in the community as a venue for socializing with friends and family, (3) Car Free Day is also a means of physical health free from pollution, (4) Car Free Day activities also make people who care about the environment that is clean and comfortable "environmentally Friendly". The downside of Car Free Day, namely: (1) the activities of the Car Free Day also has a negative impact on the smooth running of traffic because the closing part of the road will cause congestion on roads crowded alternative and (2) reduced air pollution on roads used for car Free Day but will add to air pollution in an alternative way.Designing media public service advertising campaign in the form of media that uses billboards that headline, Car Free Day, on the sub-headline, and carfree Go Do not Stop, and on the tage line, Healthy Living, Healthy Environment. Without Pollution, Without congestion. the process of designing is to create a destination as the main medium in the formof billboards and other supporting media, namely: posters, shirts, banners, pins, stickers, xbander, shopping bags, and key chains featuring the activities of the Car Free Day . Hopefully this billboard design to fruition in line with the expectations.Keywords: Public Service, Car Free Day, Billboards